The effect of attitude on Jawi acceptance among Malaysian Citizen: Indian perspectives : Wan Hashridz Rizal bin Wan Abu Bakar - Hashridz Rizal, Wan (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2021)
The use of jawi scripts is increasingly underused by the Malaysian law. Jawi has been replaced by Rumi and English writings for official purposes such as administrative affairs and so on. Jawi are still used in Islamic Education subjects at national schools, and jqaf programs. However, studies have found that there are still problems in terms of the ability, interest and motivation of students and communities to read Jawi writing materials. According to Perlis Mufti Datuk Dr Asri Zainul Abidin in Berita Harian 9 0gos 2019 states that non-Muslims consider the writings Jawi at school as if student was being applied to Islamic religious. This causes non-Muslims in Malaysia feel phobia and trauma if Jawi to be introduced in the school textbook has a link with Islam. Therefore this study aims to identify the effect of attitude on jawi in explaining the intention of Jawi acceptance among Indian community in Malaysia. This study was conducted with a total of 192 respondents. The sampling technique used is non-probability sampling. The findings of the study prove that attitude has a positive and significant relationship with the effect on Jawi acceptance among Indian.